HOMOEOPATHIC MANAGEMENT OF CUTANEOUS WARTS BASED ON INDIVIDUALIZATION: A CASE SERIES - DR SIMI POULOSE,; DR ASHRITHA B.A,; DR SHANTIPRIYA,; DR. VEERABHADRAPPA C.,; DR MAHABUBALI NADAF, (The Bioscan, 2026)
Warts are common benign cutaneous proliferations caused by infection with the human papillomavirus (HPV) and reflect an interaction between viral exposure, host immunity, and individual susceptibility. They can occur at any age, presenting in various morphological forms such as filiform, mucosal, and common warts, often causing cosmetic concern, discomfort, and psychological distress. Conventional management primarily involves topical agents or surgical removal; however, recurrence and adverse effects remain challenges. Homoeopathy emphasizes an individualized approach that addresses both the local manifestation and the underlying constitutional imbalance, particularly within the sycotic miasmatic background. This article presents three clinically documented cases of warts managed successfully with individualized homoeopathic remedies. The cases included common warts. Remedy selection was based on detailed case analysis, totality of symptoms, and miasmatic consideration. The prescribed remedies were Nitric acid, Lachesis, and Thuja occidentalis, administered according to homoeopathic principles. All cases demonstrated significant clinical improvement with complete resolution of lesions and no recurrence during follow-up, highlighting the effectiveness and safety of individualized homoeopathic management. These case outcomes support the role of homoeopathy as a cost-effective, non-invasive therapeutic option for warts, promoting holistic healing and immune balance. Further controlled studies are recommended to validate these findings. Keywords Warts, Human Papilloma Virus, Individualisation, Homoeopathy, Individualized Homoeopathic Remedy, Nitric Acid, Lachesis, Thuja Occidentalis